Entitled to embezzlement? The case of successful executives working for rich heirs - Gottschalk, Petter (Deviant behavior, 2020)
In family firms, there is a distinction between family members and nonfamily members. Research reviewed in this article indicates that family firms tend to be operated to enhance the well-being of owning families and their members. Nonfamily executives are often treated as second-class individuals in the organization. There is an asymmetrical distribution of power among family and nonfamily. From the theory of convenience, we apply equity theory in the motivational dimension, principal-agent theory in the opportunity dimension, and neutralization theory in the willingness dimension to shed light on deviant behaviors by nonfamily executives in family firms. We present two case studies from Norway - a former CEO and a former CFO in family firms - who both were sentenced to prison for embezzlement.